2012
DOI: 10.1007/s00265-011-1309-9
|View full text |Cite
|
Sign up to set email alerts
|

Intrasexual competition, territoriality and acoustic communication in male strawberry poison frogs (Oophaga pumilio)

Abstract: In many species male reproductive success is limited by access to females. Territoriality is one behavioural strategy which helps to acquire females. In the present study, we investigated the correlation between territory size and (1) female availability and (2) rate of intrusion by conspecific males in strawberry poison frogs, Oophaga pumilio. Males defended smaller territories in areas with a high female density and high rate of intrusion by conspecific males. Only males with high body condition values were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 42 publications
2
27
0
3
Order By: Relevance
“…In support for this view, we found, at least in a study shown that chicks used slight differences values in frequency to recognize adults rather than amplitude modulation [15]. This speculation also strengthened by the fact that dominant frequency is more likely used by many species of frogs to access their opponents or mates [16][17][18]. Therefore, it could possibly be the reason why dominant frequency was categorized as static in almost all studies, but it was statistically potential for individual discrimination.…”
Section: Individual Variationsupporting
confidence: 52%
“…In support for this view, we found, at least in a study shown that chicks used slight differences values in frequency to recognize adults rather than amplitude modulation [15]. This speculation also strengthened by the fact that dominant frequency is more likely used by many species of frogs to access their opponents or mates [16][17][18]. Therefore, it could possibly be the reason why dominant frequency was categorized as static in almost all studies, but it was statistically potential for individual discrimination.…”
Section: Individual Variationsupporting
confidence: 52%
“…Males use advertisement calls to attract females, and advertisement calls, aggressive calls and physical combat to defend their territories against intruding males. Males compete for access to mating partners and their distribution depends on the distribution of the females [49,55] while females defend feeding territories [69] and are limited in their distribution to areas with sites suited for tadpole-rearing [55]. In our study population females possess large overlapping home ranges (~36 m 2 ; covering several male territories) but smaller territories (~2 m 2 ) than males (~15 m 2 ) [49,55,69].…”
Section: Introductionmentioning
confidence: 99%
“…que estos machos deberían presentar igualmente una mejor condición corporal respecto a los machos de áreas con menor densidad (Meuche et al 2012).…”
Section: (R Core Team 2013)unclassified
“…Los machos defienden territorios con sitios para actividades de vocalización y para la oviposición, así como con disponibilidad de las bromelias (McVey et al 1981, Donnelly 1989, su disposición espacial depende de la distribución de las hembras, que a su vez están asociadas con sitios de desarrollo larval (Pröhl y Berke 2001). Los machos de O. pumilio compiten vigorosamente por áreas con alta densidad de hembras (Pröhl y Berke 2001), lo que implica que estos tengan mejor condición corporal respecto a los machos de áreas con menor densidad (Meuche et al 2012). De acuerdo con Meuche et al (2012) los machos con valores más altos de condición corporal podrían entonces establecer territorios con mayor densidad de hembras y alta competencia intrasexual, sin embargo, a la fecha no existe información específica para la especie que sustente esta hipótesis.…”
unclassified
See 1 more Smart Citation